The Thought of Sibawaih, Ibn Madha, and William Wright in the Contribution of Ilm al-Nahwi (Epistemological Comparative Study): ØªÙÙƒÙŠØ± Ø³ÙŠØ¨ÙˆÙŠÙ‡ ÙˆØ§Ø¨Ù† Ù…Ø¶Ø§Ø¡ Ùˆ ÙˆÙŠÙ„ÙŠØ§Ù… Ø±Ø§ÙŠØª ÙÙŠ Ù…Ø³Ø§Ù†Ø¯Ø© Ø¹Ù„Ù… Ø§Ù„Ù†ØÙˆ (Ø¯Ø±Ø§Ø³Ø© Ù…Ø¹Ø±ÙÙŠØ© Ù…Ù‚Ø§Ø±Ù†Ø©) - Hijjah, Shifany Mualida; Raswan, Raswan (STUDI ARAB, 2023)
This study aims to describe the nahwu epistemology of Imam Sibawaih, Ibn Madha, and William Wright. Different views on these principles will have an impact on differences in understanding and views in ilm al-Nahwi. The method used in this research is to use a qualitative method by describing the nahwu epistemology of Imam Sibawaih, Ibn Madha, and William Wright. For data retrieval and collection, the author uses library research because the data sources are reference books, and articles from online libraries, and online journals related to the theme of the article. The results of this study, Sibawaih in formulating the rules of nahwu used all the epistemological methods of nahwu (ushul al-nahwi), while Ibn Madha rejected the methods of qiyas and ta'lil. Nor does Wright use the method of qiyas and ta'lil in compiling his monumental work on nahwu which is popular among orientalists.